»Tvang er den sande Friheds Grundstøtte«. Civilisation og kontrol i den danske oplysningstids strafforståelser belyst ved Kriminal-Lovgivnings Kommissionen af 24. oktober 1800. - Nipper Nielsen, Signe (Historisk Tidsskrift, 2013)
»Coercion is the Foundation of True Liberty«. Civilisation and Control in the Understandings of Punishment in the Danish Enlightenment illustrated by The Commission of Criminal Legislation of 24th of October 1800.The »Commission of Criminal Legislation«, which was set up in the year 1800, was supposed to establish the foundation of a new Danish criminal Statute Book. Although the recommendations of the Commission were never really implemented, it can be seen as a token of Enlightenment, secularised criminal thought in Denmark, which was highly influenced by preceding and contemporary European currents.The Commission consisted of several prominent Danish jurists who all contributed with their own recommendations, which were eventually gathered and adopted in a final report of the 27th of October 1803.I have considered two main themes in the source material, namely social control as motive in the law-making process on the one hand, and change in sensibilities as a contributory factor, on the other hand. Here, the theories of the French philosopher Michel Foucault and the German sociologist of culture, Norbert Elias, respectively, are relevant to the understanding of the Danish Commission. Yet, their assumptions can also be questioned on the basis of the empirical material.In Discipline and Punish, Foucault observes how power manifests itself within the different systems of punishment. In Foucault’s interpretation, what has been understood as a leniency of punishment, which develops roughly from the end of the Eighteenth century onwards, is analysed as a new technology of power. In the beginning of the 18th century, the penal system, which was built on the old monarchical law, involved an unsystematic, often physically violent, arbitrary punishment with a strong public element. With a radical break at the end of the 18th and the beginning of the 19th century, disciplinary punishment with the modern penitentiary as its fulcrum takes over. Yet, an interlude between these two forms of punishment was the unimplemented penal programmes of the reforming jurists of the middle and late 18th century. These programmes were supposed to establish a penal system that should make use, not of physical marks, but of signs and coded sets of representations. Foucault maintains that the reforming jurists looked askance at the penitentiary, which was not an appropriate instrument in a penal system that revolved around a clear language and an unambiguous message. The prison was according to Foucault perceived as having a concealed, opaque nature. Further, the prison entailed a privatisation of punishment, excluding the spectators as an important element.Elias himself has not written explicitly about the history of punishment, but provides the theoretical framework and concepts, used by the Dutch historian Pieter Spierenburg. For Spierenburg, »sensibility«, understood as verifiable expressions of anxiety or repugnance, is a main factor in the change of the forms of punishment in European history. The emotional engagement of the spectators of public executions changes over time and people begin to feel abhorrence when faced with corporal punishment. Therefore, the penal laws had to change to correspond to people’s changing sensibility, and a leniency in the methods of punishment took place, especially throughout the 18th century.In the Danish Criminal Commission several positions seem to be at work. The inspiration from Cesare Beccaria, Gaetano Filangieri, P.J.A. Feuerbach and John Howard, respectively, is obvious, even if these European thinkers of the 18th and early 19th centuries had very different views of the purposes and basic principles of punishment.The final recommendations of the Commission propose, among other things, a limited employment of capital punishment and abrogation of the accompanying torture, abolishment of fortification work and »slavery« in favour of the use of forced labour and houses of correction, and improvement of the conditions of the latter. Moreover, the Commission recommended the abolishment of mutilating, corporal punishment.To simplify, in Foucault’s eyes, these proposals of a more lenient penal code are mere manifestations of a wish for more social control, whereas for Norbert Elias they would indicate a new economy of emotions, an altered sensibility. The members of the Danish Commission seem to build their arguments on both themes: social control and a more »civilised« sensibility. However, throughout the Commission the references to the aversion for cruelty - a particular emotional »delicacy« - seem to be linked to more rationally motivated considerations. Thus, instead of a regard for the »humanity« of the convict, the references to humaneness seem to be a rhetorical strategy in order to obtain something else. The members of the Commission do consider the risk of the convict being an object of compassion rather than aversion when exposed to corporal punishment. Thus, the punishment does not have its desired effect. Further, mutilating punishment, for instance, is regarded as bearing the impress of barbarity by the Commission. This is liable to have a deteriorating effect on the reputation of the judicial system. There are also socioeconomic considerations to take account of, hence the idea of easing the process of re-socialisation by for instance avoiding dismemberment. The state needs productive labour.These suggested measures can also be due to a growing sympathy and inter-human identification of the citizens, perhaps even caused by an increased interdependence between people, as Elias sees it. But there can be many other explanations of these reactions and there is moreover not much valid evidence that these feelings were really new. Moreover, it can be discussed whether it is feasible at all for the historian to work with such a volatile and complex concept as emotions.Michel Foucault’s ideas of the radical break in the history of the modern prison is unsupported in the Danish Commission in so far as the Danish reformers do see the penitentiary as a useful form of punishment, especially if the conditions in the Danish prisons were improved.Both references to emotions and to social control seem to be at play in the language of the Danish Commission. However, speculations about the »materiality« and authenticity of a certain sensibility appear to be idle, at least in the reading of this commission.